Systematic Literature Review: Perilaku Agresif pada Remaja yang Ditinjau dari Pendekatan Psikologi Biopsikologi dan Humanistik - Taufiq Nur Wicaksono; Nina Fitriana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study focuses on how adolescents can behave aggressively as reviewed from a biopsychological and humanistic approach. This study uses a literature study method, in this case the researcher looks for references from articles, books, and other references that are in accordance with the discussion of the researcher's article material. Aggressive behavior is caused by genetics, neurotransmitters, the brain, and hormones. individuals with a family history of aggressive problems are more likely to show similar behavior, indicating a hereditary component in aggression, and with low serotonin levels tend to behave aggressively, because serotonin functions in regulating emotions. At the adolescent stage, they really need affection and attention from their family. If they do not get affection and attention, adolescents will take action to be noticed by their parents, one of these actions is aggressive behavior. The ego's need for self-esteem in adolescents arises when treated unpleasantly with aggressive behavior.